2021
DOI: 10.1101/2021.11.09.21266092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebellar and Prefrontal Structures Associated with Executive Functioning in Pediatric Patients with Congenital Heart Defects

Abstract: ObjectiveChildren, adolescents, and young adults with congenital heart defects (CHD) often display cognitive and behavioral manifestations of executive dysfunction. We consider the prefrontal and cerebellar brain structures as mechanisms for executive dysfunction among those with CHD.Method55 participants with CHD (M age = 13.93) and 95 healthy controls (M age = 13.13) completed magnetic resonance imaging (MRI) of the brain, from which we extracted volumetric data on prefrontal and cerebellar regions. Particip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…al found that preterm infants with exposure to morphine in the neonatal period had decreased cerebellar volumes and worse neurodevelopmental outcomes. 79 Additionally, our group has previously shown that CHD children with reduced cerebellar volumes scored worse in tests for working memory, inhibitory control, and mental flexibility 80 . We also demonstrated that the superior surface of the cerebellum, primarily composed of the posterior lobe and the midline vermis, is an area particularly susceptible to alterations in morphology, indicating possible regions specifically affected by dysmaturation in CHD.…”
Section: Discussionmentioning
confidence: 98%
“…al found that preterm infants with exposure to morphine in the neonatal period had decreased cerebellar volumes and worse neurodevelopmental outcomes. 79 Additionally, our group has previously shown that CHD children with reduced cerebellar volumes scored worse in tests for working memory, inhibitory control, and mental flexibility 80 . We also demonstrated that the superior surface of the cerebellum, primarily composed of the posterior lobe and the midline vermis, is an area particularly susceptible to alterations in morphology, indicating possible regions specifically affected by dysmaturation in CHD.…”
Section: Discussionmentioning
confidence: 98%